An overview of carbohydrate-based carbonic anhydrase inhibitors - Doretta Cuffaro; Elisa Nuti; Armando Rossello (Taylor & Francis Group, 2020)
Carbonic anhydrases (CAs) are metalloenzymes responsible for the reversible hydration of carbon dioxide to bicarbonate, a fundamental reaction involved in various physiological and pathological processes. In the last decades, CAs have been considered as important drug targets for different pathologies such as glaucoma, epilepsy and cancer. The design of potent and selective inhibitors has been an outstanding goal leading to the discovery of new drugs. Among the different strategies developed to date, the design of carbohydrate-based CA inhibitors (CAIs) has emerged as a versatile tool in order to selectively target CAs. The insertion of a glycosyl moiety as a hydrophilic tail in sulfonamide, sulfenamide, sulfamate or coumarin scaffolds allowed the discovery of many different series of sugar-based CAIs, with relevant inhibitory results. This review will focus on carbohydrate-based CAIs developed so far, classifying them in glycosidic and glycoconjugated inhibitors based on the conjugation chemistry adopted.